2018
DOI: 10.1128/mbio.01346-18
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the Interaction between the Bacterial Cell Division Proteins FtsQ and FtsB

Abstract: In most bacteria and archaea, filaments of FtsZ protein organize cell division. FtsZ forms a ring structure at the division site and starts the recruitment of 10 to 20 downstream proteins that together form a multiprotein complex termed the divisome. The divisome is thought to facilitate many of the steps required to make two cells out of one. FtsQ and FtsB are part of the divisome, with FtsQ being a central hub, interacting with most of the other divisome components. Here we show for the first time in detail … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 43 publications
7
67
0
Order By: Relevance
“…S3). Consistently, the electron density map of FtsB N-terminus (residues 22–63) was not observed for FtsB in the crystal structure of FtsQB complex, which was reported recently by other group 26 . One possibility regarding the lack of electron density is that the membrane-proximal helix is disordered in the crystal of FtsQB complex; however, the crystal structure of the 30 juxta-membrane amino acids of FtsB showed that it forms a canonical coiled coil 27 , thus we excluded this possibility.…”
Section: Resultssupporting
confidence: 89%
“…S3). Consistently, the electron density map of FtsB N-terminus (residues 22–63) was not observed for FtsB in the crystal structure of FtsQB complex, which was reported recently by other group 26 . One possibility regarding the lack of electron density is that the membrane-proximal helix is disordered in the crystal of FtsQB complex; however, the crystal structure of the 30 juxta-membrane amino acids of FtsB showed that it forms a canonical coiled coil 27 , thus we excluded this possibility.…”
Section: Resultssupporting
confidence: 89%
“…TolB plays a role in OM invagination during cell constriction in the trans-envelope Tol-pal system (Zhuang et al, 2002;Gerding et al, 2007;Ridley and Lakey, 2015). The Fts opera, containing FtsA, FtsI, FtsL, and FtsQ, are involved in cell division (Chen and Beckwith, 2001;Kureisaite-Ciziene et al, 2018;Du et al, 2019). MrcA and MurA play a role in cell wall formation (Kock et al, 2004;Zhu et al, 2012), Tig is involved in protein export, and the only downregulated protein in the 11 proteins related to cell division (Martinez-Hackert and Hendrickson, 2009).…”
Section: Bioinformatics Analysis On the Cell Division And Cell Wall Bmentioning
confidence: 99%
“…They also interact with FtsQ through their C-terminal domains that lie beyond the coiled-coil domains forming a 1:1:1 complex which may dimerize (13,15,18). Recently, a peptide corresponding to the C-terminal region of FtsB was crystallized bound to FtsQ (19,20).…”
Section: Introductionmentioning
confidence: 99%